Esophago‐gastric motility and nutritional management in a child with ATR‐X syndrome. Issue 4 (August 2014) - Watanabe, Toshihiko; Arai, Katsuhiro; Takahashi, Masataka; Ohno, Michinobu; Sato, Kaori; Fuchimoto, Yasushi; Wada, Takahiko; Ida, Shinobu; Kawahara, Hisayoshi; Kanamori, Yutaka
Abstract X‐linked alpha thalassemia mental retardation (ATR‐X) syndrome is an X‐linked recessive disorder that often involves gastrointestinal symptoms. Aspiration pneumonia related to gastroesophageal reflux has been reported as the major cause of death, but gastrointestinal function has not been well investigated. The present report describes a child with ATR‐X syndrome who suffered from periodical episodes of refractory vomiting. We investigated the function of upper alimentary tract and found that esophago‐gastric dysmotility and severe gastric volvulus were the major causes of gastrointestinal symptoms. This child was surgically treated with anterior gastropexy and jejunal alimentation through gastrostomy, and the symptoms were relieved with good weight gain. This report may provide insight into the gastrointestinal function and nutritional management in children with ATR‐X syndrome.